2020
DOI: 10.1111/gcb.15401
|View full text |Cite
|
Sign up to set email alerts
|

Elevation alters outcome of competition between resident and range‐shifting species

Abstract: Species’ geographic range shifts toward higher latitudes and elevations are among the most frequently reported consequences of climate change. However, the role of species interactions in setting range margins remains poorly understood. We used cage experiments in ponds to test competing hypotheses about the role of abiotic and biotic mechanisms for structuring range boundaries of an upslope range‐shifting caddisfly Limnephilus picturatus. We found that competition with a ubiquitous species Limnephilus externu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 76 publications
(125 reference statements)
4
24
0
Order By: Relevance
“…For all focal species, the SDMs predicted substantial amounts of suitable habitat beyond their current ranges, indicating that species' potential ranges are considerably larger than their realized ranges. These results corroborate previous modelling and experimental work, suggesting that also non‐climatic factors are important in setting range limits (Louthan et al, 2015; Sanczuk et al, 2022; Shepard et al, 2021). For example, Svenning et al (2008) showed that the ranges of many plants native to European forests are still subject to post‐glacial dispersal limitation (Svenning et al, 2008).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…For all focal species, the SDMs predicted substantial amounts of suitable habitat beyond their current ranges, indicating that species' potential ranges are considerably larger than their realized ranges. These results corroborate previous modelling and experimental work, suggesting that also non‐climatic factors are important in setting range limits (Louthan et al, 2015; Sanczuk et al, 2022; Shepard et al, 2021). For example, Svenning et al (2008) showed that the ranges of many plants native to European forests are still subject to post‐glacial dispersal limitation (Svenning et al, 2008).…”
Section: Discussionsupporting
confidence: 91%
“…These results corroborate previous modelling and experimental work, suggesting that also non-climatic factors are important in setting range limits (Louthan et al, 2015;Sanczuk et al, 2022;Shepard et al, 2021). For example, Svenning et al (2008) showed that the ranges of many plants native to European forests are still subject to post-glacial dispersal limitation (Svenning et al, 2008).…”
Section: It Was Remarkable That Estimates Of Population Growth Insupporting
confidence: 90%
See 3 more Smart Citations